Economic efficiency of investments in fruits processing - Iuliana Dobre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The aim of this paper is to find out the economic efficiency of an associative unit in fruits processing and trading field. In this order a scenario by loan is taken into consideration. Indicators such as production, incomes and expenditures, profit, also investment indicators are studied. The paper consists into the establishment of a processing fruits to prolong their life, and get products with higher value added consumer demand; establishing a network for collecting local fruits, supply of raw materials for the processing; providing storage services and marketing associative members. Technical objectives of the investment are to purchase machineries and equipments for processing apples and plums; the purchase of land for their location, building factory and deposit. The financial objectives refer to investment. The results show the relevance of associative units for producer integrating and investment feasibility.
Keywords: Q13; 330; associative unit; fruits processing; investment; economic efficiency